HERMENEUTIKA KHALED M. ABOU EL FADL TENTANG KONSEP OTORITARIANISME DALAM HUKUM ISLAM - Muhammad Islahuddin (LPPM STAI Muhammadiyah Probolinggo, 2019)
Khaled M. Abou el-Fadl is one of the contemporary Islamic thinkers who offers a model of reading religious texts which he considers authoritative. The phenomenon of authoritarianism or self-determination in the name of religion and God in Islamic thought, according to Khaled M. Abou el-Fadl, happens a lot as evidenced in his research which focuses on the study of Islamic law that has been carried out by Wahabi puritans in the CRLO fatwa institutions that provide many fatwas which is considered to be very gender biased. Khaled M. Abou el-Fadl offers authoritative hermeneutics as a criticism as well as a methodological tool for dissecting and interpreting Islamic texts, specifically in the realm of Islamic law, namely by paying attention to three things, First, relating to competence (authenticity test); second, related to accuracy; third, with regard to representation in Islam